In-depth profiling of drug resistance to PI3K-mTOR inhibition and intra-tumour heterogeneity in NSCLC - Elbai, Samira Mohamed (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2021)
Lung cancer has an overall 5-year survival rate of less than 15% and is the leading cause of cancer-related death worldwide. As such, it is crucial we develop new treatment strategies to overcome this formidable disease. In 2004, the discovery of EGFR mutations that confer sensitivity to EGFR tyrosine kinase inhibitors in lung adenocarcinomas heralded the beginning of the era of precision medicine for lung cancer. The concerted effort to define molecular subgroups of lung cancer and identify novel therapeutic targets has significantly impacted the advancement of lung cancer treatment and patient survival. However, the clinical application of molecularly guided personalized treatment is challenging. The biggest hurdle is the inevitable emergence of drug resistance that ultimately renders therapy ineffective. Tumour cells have the innate ability to employ different mechanisms to resist the targeting agent, often driven by the heterogeneous nature of tumours, which is especially prevalent in lung cancer. The PI3K-mTOR signalling pathway together with AKT phosphorylation is active in 50-70% of non-small cell lung cancer (NSCLC) and plays an overarching role in all the hallmarks of cancer, including evading immune destruction. Pathway dysregulation confers a poor prognosis making it an ideal target for treatment. Results from early-phase PI3K targeted therapy clinical trials have been mixed, with innate and acquired resistance to PI3K inhibition anticipated to be a major hurdle to overcome in the development of these drugs. Initial efforts to therapeutically target the PI3K-mTOR pathway in NSCLC have resulted in only a few partial responses; however, most of the Phase I studies did not select for patients with an activated PI3K-mTOR pathway. Several clinical trials combining a PI3K inhibitor with another targeted therapy or immunotherapy are currently recruiting. This project set out to further identify and validate biomarkers of drug resistance to PI3K-mTOR targeted therapies to guide clinicians in the design of improved treatment strategies for patients. Our group previously developed NSCLC cell line models of acquired resistance to PI3K-mTOR inhibitor apitolisib which were used in this study to validate specific bypass mechanisms of resistance. In-depth analysis of differentially expressed mRNAs and lncRNAs identified changes in genes involved in the regulation of metabolism and cellular response to stimuli. We are the first to show that inhibition of PI3K-mTOR in NSCLC leads to transcriptional activation of PIM1, PIM2 and PIM3 kinases as well as c-Myc. Activated MACC1 expression was confirmed as an early event in the emergence of drug resistance, suggesting it may be involved in initiating the events leading to the upregulation of other genes such as MYC, PIM1/2/3 and the acquired resistance to PI3K/mTOR inhibitors. Dual PIM kinase and PI3K-mTOR inhibition decreases cell proliferation, and this data provides a rationale for co-targeting treatment strategies for patients with tumours that have a dysregulated PI3K-mTOR pathway. This personalized medicine approach will improve response rates and survival benefits for patients with NSCLC. The second part of this thesis examined proteomic, phospho-proteomic, genomic and transcriptomic intra-tumour heterogeneity (ITH) to determine differences in the molecular profile of cancer cells within the tumour and in particular how this may affect the diagnosis and stratification of patients for personalized treatment. Proteomic and phospho-proteomic expression was quantified across three different regions of the same tumour and matched normal tissue from four patients with lung squamous cell carcinoma. Label-free L-C/MS-MS comparative proteomics and principal component analysis was performed and demonstrated heterogeneous expression of proteins between different areas of the same tumour mass. Interestingly, for the most part protein expression was identified in all tumour regions, albeit differentially expressed. A panel of four differentially expressed proteins (Enolase-1, desmoplakin, tenascin C and EROI-La) were selected for further validation by western blot analysis in the same protein samples. Phosphorylated proteins demonstrated a more divergent expression pattern between different areas of the same tumour with some undetectable in one area while present in another part of the tumour. It was unclear whether this lack of expression was a true reflection of tumour biology or may have been due to the instability of phosphorylated proteins. Finally, whole exome sequencing (WES) and a microarray for RNA and lncRNA profile analysis were used to quantify genomic and transcriptomic ITH respectively, across two different tumour regions and matched normal tissue from three patients with lung adenocarcinomas. The number of uniquely mutated genes per tumour region in all tumours infers a high level of heterogeneity. The microarray dataset identified novel lncRNA expression profiles in lung cancer that warrant further investigation for the identification of biomarkers and new therapeutic targets that can be used for NSCLC treatment. In summary, ITH and clonal evolution enable the survival of residual disease cells that eventually cause tumour relapse and the failure of single-agent-targeted inhibitors to induce long-lasting durable responses to treatment. Our data further highlights the limitations of tumour tissue biopsies to predict molecular or proteomic profiles. Therefore, a panel of biomarkers allows for better patient stratification for personalized targeted treatment.
APPROVED
Keywords: Lung cancer, drug resistance markers, intra-tumour heterogeneity.